Iron-rich manganese-based positive electrode material as well as preparation method and application thereof

An iron-rich manganese-based electrode material with radially stacked rod-shaped particles addresses the stability and performance issues of sodium-ion batteries, offering enhanced cycle stability and cost-effectiveness through a novel synthesis method.

CN119170799APending Publication Date: 2024-12-20WUHU JIANA ENERGY TECHNOLOGY CO LTD +3
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411308617.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Existing sodium-ion battery positive electrode materials face challenges in achieving high electrochemical performance and structural stability simultaneously, with layered oxide materials having a low cost-performance ratio due to the use of nickel and issues with primary particle stability.

Method used

Development of an iron-rich manganese-based positive electrode material with thick rod-shaped primary particles arranged in a divergent orientation, formed into secondary spherical or quasi-spherical particles, utilizing a specific molecular formula and a precipitation reaction followed by sintering to enhance structural stability and sodium ion diffusion.

Benefits of technology

The material provides improved cycle stability and rapid sodium ion transmission, maintaining structural integrity while reducing the need for costly nickel, thus enhancing the cost-performance ratio of sodium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170799A_ABST
    Figure CN119170799A_ABST
Patent Text Reader

Abstract

The invention provides an iron-rich manganese-based positive electrode material as well as a preparation method and application thereof, and relates to the technical field of sodium ion batteries. Specifically, the iron-rich manganese-based positive electrode material disclosed by the invention is secondary spherical particles or secondary sphere-like particles formed by closely packing primary particles with rod-shaped structures, and the packing is in divergent orientation arrangement; the molecular formula of the iron-rich manganese-based positive electrode material is Na [delta] Fe [gamma] Mn [beta] M [alpha] O2, M comprises at least one of Ni, Ca, Zn, Co, Mg, Al or Ti, and a series of numerical limits on [delta], [gamma], [beta] and [alpha] exist. According to the invention, the sodium battery positive electrode material with excellent electrochemical performance and excellent secondary particle structure stability is obtained through adjustment of the element composition of the positive electrode material and a co-modification strategy of radial stacking of microscopic primary particle morphology, and the sodium battery positive electrode material has excellent rate capability and cycling stability and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to an iron-rich manganese-based positive electrode material and a preparation method and application thereof. Background Art

[0002] With the sharp drop in the prices of lithium carbonate and lithium hydroxide, the prices of lithium-ion battery cathode materials, including ternary materials or lithium iron phosphate materials, have also dropped significantly; especially lithium iron phosphate, which has been widely used in the energy storage industry and power field after the price drop. In sharp contrast, sodium-ion batteries are slow to be promoted due to the dual impact of cost and performance.

[0003] At present, common positive electrode materials for sodium-ion batteries mainly include layered oxides, Prussian blue compounds, polyanion compounds, etc. At this stage, the capacity of Prussian blue compounds and polyanion compounds is lower than that of layered oxides. In order to further improve the material capacity of layered oxides, nickel elements are widely introduced, resulting in a weaker cost-performance ratio between cost and performance than lithium iron phosphate materials. If the use of a large amount of nickel can be abandoned and the development of manganese-rich or iron-rich layered oxide positive electrode materials can be turned to, and the performance and stability of the materials can be enhanced, the cost-performance ratio of layered oxide positive electrode materials can be significantly improved.

[0004] In order to improve the electrochemical performance and stability of layered oxide positive electrode materials, the existing technology has conducted extensive research; for example: preparing the positive electrode material into the morphology of single crystal particles to highlight the structural stability, and proposing the use of radiating or radially distributed microstructures to provide a fast channel for sodium ions, thereby improving the performance of the material; however, the primary particles are fine and the stability of the primary particles is weak. For another example, researchers proposed to use a certain proportion of polycrystalline spherical particles and single crystal particles as positive electrode materials to achieve a balance between performance and stability; for another example, the application of single crystal-like materials can also enable the positive electrode material to have both high performance and structural stability; however, it relies on smaller primary particles and lacks radial structures.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The first purpose of the present invention is to provide an iron-rich manganese-based positive electrode material, which is mainly used to solve the technical problems that the electrochemical performance and microstructural stability of the layered oxide positive electrode materials of sodium ion batteries cannot be taken into account at the same time, and the material has a low cost performance when the performance and stability are enhanced at the same time; the present invention develops a polycrystalline particle-type iron-rich manganese-based oxide positive electrode material composed of thick rod-shaped primary particles with a high ring diameter, and the primary particles present a divergent radial distribution, while giving it high performance and a stable structure, and at the same time has important research and application significance for the development of low-cost sodium ion batteries.

[0007] The second purpose of the present invention is to provide a method for preparing the iron-rich manganese-based positive electrode material. The synthesis method is simple and can be applied to the existing ternary precursor production equipment, and is easy to realize large-scale batch production.

[0008] A third object of the present invention is to provide a sodium ion battery.

[0009] A fourth object of the present invention is to provide an electrical device.

[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0011] An iron-rich manganese-based positive electrode material, which is a secondary spherical particle or a secondary quasi-spherical particle formed by closely stacking primary particles of a rod-like structure, wherein the stacking is arranged in a divergent orientation;

[0012] The molecular formula of the iron-rich manganese-based positive electrode material is Na δ Fe γ Mn β M α O2, M includes at least one of Ni, Ca, Zn, Co, Mg, Al or Ti, 1.0≥δ≥0.4, 0.65≥γ≥0.4, 0.7≥β≥0.4, 0.10≥α>0, 2.1>δ+γ+β+α>1.3;

[0013] 3*γ+(3+z)*β+(2+2z)*α+δ=4, where z satisfies: 1≥z≥0.

[0014] A method for preparing the iron-rich manganese-based positive electrode material comprises the following steps:

[0015] A mixed solution containing an iron source and a manganese source is prepared, and a doping solution containing a doping element source is prepared; the mixed solution, the doping solution, a complexing agent and a precipitant are simultaneously introduced to perform a precipitation reaction and obtain a precursor; the precursor is mixed with a sodium source and then sintered to obtain an iron-rich manganese-based positive electrode material.

[0016] A sodium ion battery comprises the iron-rich manganese-based positive electrode material.

[0017] An electrical device comprises the sodium ion battery.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] The present invention provides a thick rod-shaped and radially stacked iron-manganese-rich layered positive electrode material for sodium ion batteries, and proposes a corresponding preparation process. The positive electrode material of the present invention is based on iron-rich, manganese-rich and a small amount of doping elements, relying on carbonate in the precipitant and ferrous ions and divalent manganese ions in a synthetic environment of a specific coprecipitation liquid phase to form a uniquely oriented growth of thick rod-shaped primary particles, and assemble to obtain a precursor of polycrystalline spherical / quasi-spherical large particles; further, the precursor is mixed with a sodium salt, and combined with a suitable high-temperature roasting treatment to inhibit the melt growth between the grains, to obtain a radially structured ordered iron-manganese-rich layered positive electrode material for sodium ion batteries.

[0020] The iron-rich manganese-based cathode material of the present invention not only maintains the radial structural orientation of the precursor, but also promotes the rapid embedding and transmission of sodium ions along the diffusion channel from the inside to the outside; at the same time, the micron-sized thick rod-shaped primary particles have a more stable structure, and combined with the ion doping effect of M, the Mn 3+ The Jahn Teller effect brought about by the metal-oxygen bond strengthens the skeleton structure of the layered lattice, further improving the cycle stability of the positive electrode material. In addition, Fe and Mn in the positive electrode material of the present invention are cheap and abundant in reserves, and the amount of doping elements is relatively low, which effectively avoids the problem of morphological structural distortion caused by the large amount of non-Fe and Mn elements added. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 A microscopic schematic diagram of an iron-rich manganese-based positive electrode material is provided;

[0023] Figure 2 Provides a SEM image of the precursor of Example 1;

[0024] Figure 3 Provides a SEM image of the positive electrode material of Example 1;

[0025] Figure 4 A SEM image of the positive electrode material of Comparative Example 1 is provided;

[0026] Figure 5 Provides a SEM image of the precursor of Comparative Example 2;

[0027] Figure 6 Provides a SEM image of the precursor of Comparative Example 3;

[0028] Figure 7 The SEM image of the precursor of Comparative Example 4 is provided. DETAILED DESCRIPTION

[0029] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but those skilled in the art will appreciate that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially. In addition, the terms "first", "second" and "third" are only used for descriptive purposes and cannot be interpreted as indicating or implying relative importance.

[0030] A first aspect of the present invention is to provide an iron-rich manganese-based positive electrode material.

[0031] The iron-rich manganese-based positive electrode material is a secondary spherical particle or a secondary quasi-spherical particle formed by closely stacking primary particles of a rod-like structure, and the stacking is arranged in a divergent orientation; the molecular formula of the iron-rich manganese-based positive electrode material is Na δ Fe γ Mn β M α O2, M includes at least one of Ni, Ca, Zn, Co, Mg, Al or Ti, 1.0≥δ≥0.4, 0.65≥γ≥0.4, 0.7≥β≥0.4, 0.10≥α>0, 2.1>δ+γ+β+α>1.3.

[0032] In addition, an equation containing another parameter z is set: 3*γ+(3+z)*β+(2+2z)*α+δ=4, and after substituting any values ​​of δ, γ, β, and α that satisfy the above restrictions into the equation containing z, the derived value of z satisfies 1≥z≥0. The present invention effectively limits the valence states of Fe, Mn, and M by limiting the range of the equation containing z and the value of z, thereby meeting the requirements for electrochemical performance and molecular structure stability.

[0033] As an optional embodiment, the value of δ includes but is not limited to any one of 0.4, 0.42, 0.45, 0.48, 0.5, 0.52, 0.55, 0.58, 0.6, 0.62, 0.65, 0.68, 0.7, 0.72, 0.75, 0.78, 0.8, 0.82, 0.85, 0.88, 0.9, 0.92, 0.95, 0.98, and 1.0, or a numerical interval consisting of any two of them.

[0034] As an optional implementation, the value of γ includes but is not limited to any one of 0.4, 0.42, 0.45, 0.48, 0.5, 0.52, 0.55, 0.58, 0.6, 0.62, and 0.65, or a numerical range consisting of any two of them.

[0035] As an optional implementation, the value of β includes but is not limited to any one of 0.4, 0.42, 0.45, 0.48, 0.5, 0.52, 0.55, 0.58, 0.6, 0.62, 0.65, 0.68, and 0.7, or a numerical range consisting of any two of them.

[0036] As an optional implementation, the value of α includes but is not limited to any one of 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, and 0.1, or a numerical interval consisting of any two of them.

[0037] As an optional implementation, the value of δ+γ+β+α includes but is not limited to any one of 1.31, 1.35, 1.4, 1.45, 1.5, 1.55, 1.6, 1.65, 1.7, 1.75, 1.8, 1.85, 1.9, 1.95, 2, 2.05, 2.09, or a numerical interval consisting of any two of them.

[0038] As a preferred embodiment, for the primary particles of the rod-like structure, the aspect ratio is 3.1 to 8.5, and the radial diameter is 0.4 μm to 0.8 μm. Figure 1 This is a schematic diagram of a coarse rod-shaped oriented iron-manganese-rich positive electrode material (and the precursor also satisfies the configuration of this schematic diagram). The primary particles in the figure have a relatively coarse ring diameter, and the primary particles are closely dispersed in the radial direction to obtain overall secondary spherical particles.

[0039] As a preferred embodiment, the iron-rich manganese-based positive electrode material is prepared by mixing and sintering a precursor and a sodium source; wherein the molecular formula of the precursor is Fe γ Mn β M α (OH) x (CO3) y , y / 2>x≥0, 2.5>2y+x≥2.

[0040] Furthermore, an inequality containing another parameter Q is set, and the parameter Q satisfies 70≥Q≥10. In this case, the inequality satisfies:

[0041] 0%≥(55.8*γ+54.9*β+Q*α) / (55.8*γ+54.9*β+Q*α+17*x+60*y)≥40%; after substituting any values ​​of δ, γ, β, and α that meet the above limitations into the Q-containing inequality, the calculation results of the Q-containing inequality are all within the above-mentioned limited thresholds. The present invention effectively limits the percentage of the sum of the total atomic masses of Fe, Mn, and M by limiting the range of the Q-containing inequality and the Q value, thereby meeting the requirements for electrochemical performance and molecular structure stability.

[0042] As a more preferred embodiment, the D50 of the precursor is 5 μm to 15 μm, and the tap density of the precursor is 1.3 g / cm 3 ~1.9g / cm 3 .

[0043] As a preferred embodiment, the D50 of the iron-rich manganese-based positive electrode material is 4.5 μm to 14.5 μm, and the tap density of the iron-rich manganese-based positive electrode material is 1.35 g / cm 3 ~1.95g / cm 3 .

[0044] As a preferred embodiment, M is classified by ion valence, M includes M2 with ion valence of +2, M3 with ion valence of +3 and M4 with ion valence of +4, and the atomic contents corresponding to M2, M3 and M4 in the iron-rich manganese-based positive electrode material are A, B and C, respectively, satisfying: A>B+C>B>C≥0. That is, the doping element M in the present invention includes several elements with different valence states, and the amount of doping elements introduced in non-+2 valence states is higher than that in doping elements in +3 and +4 valence states, which helps to increase the average valence of Mn in the iron-rich manganese-based positive electrode material and improve the stability of the positive electrode material. Specifically: a larger content of +2-valent ions in M ​​can effectively increase the valence state of Mn in the positive electrode material, inhibit the Jan-Taylor effect of +3-valent Mn ions during the charge and discharge process, and stabilize the material structure; the use of a small amount of +3-valent or +4-valent M ions can better reduce the precipitation segregation caused by the large difference in precipitation coefficients, or destroy the coarse rod-shaped morphology structure; in addition, the use of +3-valent or +4-valent M ions can further stabilize the structure and promote the performance of the positive electrode material in the voltage range of 1.5V to 4.0V.

[0045] The second aspect of the present invention is to provide a method for preparing the iron-rich manganese-based positive electrode material.

[0046] The preparation method comprises the following steps: preparing a mixed solution containing an iron source and a manganese source, and preparing a doping solution containing a doping element source; simultaneously feeding the mixed solution, the doping solution, a complexing agent and a precipitant to perform a precipitation reaction and obtain a precursor; and mixing the precursor with a sodium source and sintering the mixture to obtain an iron-rich manganese-based positive electrode material.

[0047] As a preferred embodiment, the amount of the iron source, the manganese source and the doping element source is based on the molecular formula of the iron-rich manganese-based positive electrode material Na δ Fe γ Mn β M α The proportions are based on the values ​​of γ, β, and α in O2; and the amount of the sodium source is based on (γ+β+α): (δ+0.01~0.05); it should be noted that the above proportions are based on the molar amount of the corresponding metal elements in each raw material source.

[0048] As a preferred embodiment, the iron source, the manganese source and the doping element source include but are not limited to any one or more soluble salts of chlorides, sulfates, nitrates, acetates and the like containing the corresponding metal elements.

[0049] As a preferred embodiment, the total concentration of cations in the mixed solution is 0.5 mol / L to 1.6 mol / L, and the pH of the mixed solution is 1.0 to 2.0.

[0050] As a preferred embodiment, the total concentration of cations in the doping solution is 0.05 mol / L to 1.0 mol / L, and the pH of the doping solution is 2.0 to 5.0.

[0051] As a more preferred embodiment, after configuring the mixed solution and the doping solution, the method further includes: adjusting the pH to the above-mentioned preferred pH range with an acid, wherein the acid used includes but is not limited to hydrochloric acid, sulfuric acid, nitric acid, etc.; in some optional embodiments, the mixed solution is adjusted with sulfuric acid, and the doping solution is adjusted with nitric acid.

[0052] As a preferred embodiment, the complexing agent includes at least one of ammonia water, oxalic acid, ammonium sulfate, ammonium acetate, citric acid or EDTA-2 sodium.

[0053] As a more preferred embodiment, the complexing agent is added in the form of an aqueous solution, and the concentration of the aqueous solution of the complexing agent is 0.05 mol / L to 0.5 mol / L.

[0054] As a preferred embodiment, the precipitant includes at least one of sodium carbonate, sodium bicarbonate, a combination of sodium carbonate and sodium hydroxide, a combination of sodium bicarbonate and sodium hydroxide, potassium carbonate, potassium bicarbonate, a combination of potassium carbonate and sodium hydroxide, or a combination of potassium bicarbonate and sodium hydroxide.

[0055] As a more preferred embodiment, the precipitant is added in the form of an aqueous solution, and the concentration of the aqueous solution of the precipitant is 0.5 mol / L to 2.5 mol / L.

[0056] As a preferred embodiment, the sodium source includes at least one of sodium carbonate, sodium acetate, sodium hydroxide or sodium bicarbonate.

[0057] As a preferred embodiment, the precipitation reaction includes two stages, namely, a seed preparation stage and a growth regulation stage; the seed preparation stage is within 10 hours after the start of the precipitation reaction, and the growth regulation stage is from the seed preparation stage to 150 hours after the start of the precipitation reaction.

[0058] In the seed preparation stage: the mixed solution, the doping solution, the complexing agent and the precipitant are simultaneously fed into the reaction container, the feeding amount of the precipitant is based on ensuring that the pH of the reaction system is maintained at 9.5-11, the feeding rate ratio of the mixed solution and the doping solution is (γ+β):α, the feeding amount of the complexing agent is based on the molar amount of the complexing agent, and at any reaction time, the ratio of the complexing agent to the total molar amount of Fe, Mn, and M is 0.001-0.1. The end of the reaction in this stage is controlled based on the seed D50 particle size obtained in the seed preparation stage, and the seed D50 is 0.1μm-2.5μm.

[0059] In the growth regulation stage: the mixed solution, the doping solution, the complexing agent and the precipitant are simultaneously fed into the reaction container, the feeding amount of the precipitant is based on ensuring that the pH of the reaction system is maintained at 7.3 to 9, and the feeding amounts of the mixed solution, the doping solution and the complexing agent are consistent with the seed preparation stage. The reaction of this stage is controlled to end based on the D50 particle size of the precursor obtained in the growth regulation stage, and the D50 of the precursor is 5 μm to 15 μm.

[0060] As an optional embodiment, the pH of the reaction liquid in the seed preparation stage includes but is not limited to any one of 9.5, 9.6, 9.7, 9.8, 9.9, 10, 10.1, 10.2, 10.3, 10.4, 10.5, 10.6, 10.7, 10.8, 10.9, 11, or a numerical range consisting of any two of them; the pH of the reaction liquid in the growth regulation stage includes but is not limited to any one of 7.3, 7.4, 7.5, 7.6, 7.7, 7.8, 7.9, 8, 8.1, 8.2, 8.3, 8.4, 8.5, 8.6, 8.7, 8.8, 8.9, 9, or a numerical range consisting of any two of them.

[0061] As a more preferred embodiment, the precipitation reaction temperature is 50°C to 70°C, and the precipitation reaction is carried out under stirring; in some optional embodiments, the stirring speed is 150rpm to 450rpm.

[0062] As a preferred embodiment, after the precipitation reaction, the method further comprises: subjecting the reaction liquid of the precipitation reaction to solid-liquid separation treatment, washing, drying and sieving the obtained solid phase to obtain the precursor having a limited particle size range.

[0063] As a preferred embodiment, the sintering temperature is 750°C to 900°C, and the sintering time is 8h to 20h; in some more preferred embodiments, the sintering heating rate is 1°C / min to 5°C / min.

[0064] A third aspect of the present invention is to provide a sodium ion battery.

[0065] The sodium ion battery includes the iron-rich manganese-based positive electrode material; it is understandable that the sodium ion battery should include a positive electrode, a negative electrode, an electrolyte, a separator, and other necessary or non-essential functional elements or packaging components, and the positive electrode includes a current collector, a positive electrode active material, a binder, a conductive agent, etc., and the positive electrode active material includes the iron-rich manganese-based positive electrode material; the positive electrode active material may also include other types of materials, and the present invention does not impose any restrictions thereon.

[0066] A fourth aspect of the present invention is to provide an electrical device.

[0067] The electrical equipment includes the sodium ion battery; it can be understood that the electrical equipment can be any equipment or device that relies on electric energy to work or operate, including but not limited to new energy vehicles, building electrical equipment, industrial electrical appliances, household and agricultural electrical appliances, etc.; when the sodium ion battery is included, any electrical equipment equipped with the sodium ion battery can belong to an embodiment of the present invention.

[0068] Example 1

[0069] (1) Ferrous sulfate and manganese sulfate were weighed in a molar ratio of 1:1 to prepare a 1.0 mol / L iron-manganese mixed solution, and sulfuric acid was added to ensure that its pH was 1.5; nickel sulfate was prepared into a doping solution with a concentration of 0.4 mol / L, and nitric acid was added to ensure that its pH was 2.5; the complexing agent was ammonium sulfate solution with a concentration of 1.0 mol / L; the carbonate precipitant was sodium carbonate solution with a concentration of 2.5 mol / L.

[0070] (2) The temperature in the precipitation kettle was maintained at 60° C., and nitrogen was introduced into the kettle. The pH value of the bottom liquid was adjusted to 10.0 using sodium carbonate solution. The rotation speed was 390 rpm and stirring was continued. The iron-manganese mixed solution (100 L / h), the doping solution (10 L / h), the complexing agent (5 L / h), and the carbonate precipitant were fed simultaneously to react, wherein the feed flow rate of the precipitant was based on ensuring that the pH value was 10.0±0.2. The reaction was continued for 3 h to obtain a precursor seed crystal with a D50 particle size of 1.5 μm.

[0071] (3) After the reaction of step (2) was carried out for 3 hours, the flow rate of the precipitant was appropriately reduced to reduce the pH value to 7.6±0.2, the rotation speed was adjusted to 270 rpm, and the co-flow feeding of the above-mentioned iron-manganese mixed solution and the complexing agent was continued, and the reaction was continued for 95 hours and then stopped. At this time, the target D50 particle size of 11 μm was reached; the stopped material was filtered, washed, dried, and sieved to obtain a coarse rod-shaped oriented iron-manganese-rich precursor (Fe 0.48 Mn 0.48 Ni 0.04 CO3).

[0072] (4) The precursor obtained in step (3) and sodium carbonate were weighed and mixed in a molar ratio of 1:0.35, and then heated and calcined in an oxygen atmosphere, and the temperature was raised to 850° C. at a rate of 3° C. / min and kept at this temperature for 15 h. Finally, the positive electrode material (Na 0.67 Fe 0.48 Mn 0.48 Ni 0.04 O2).

[0073] According to the molecular formula of the positive electrode material, in this embodiment, δ=0.67, γ=0.48, β=0.48, α=0.04; satisfying: 1.0≥δ≥0.4, 0.65≥γ≥0.4, 0.7≥β≥0.4, 0.10≥α>0, 2.1>δ+γ+β+α=1.67>1.3; in addition:

[0074] 3*γ+(3+z)*β+(2+2z)*α+δ=3*0.48+(3+z)*0.48+(2+2z)*0.04+0.67=4, therefore, z=0.6607, satisfying: 1≥z≥0.

[0075] Example 2

[0076] (1) Ferrous sulfate and manganese sulfate were weighed in a molar ratio of 1:1 to prepare a 1.0 mol / L iron-manganese mixed solution, and sulfuric acid was added to ensure that its pH was 1.9; zinc sulfate, aluminum nitrate, and titanium tetrachloride were weighed in a molar ratio of 5:2:1 to prepare a doping solution with a concentration of 1.0 mol / L, and sulfuric acid was added to ensure that its pH was 2.2; the complexing agent was an oxalic acid solution with a concentration of 1.0 mol / L; the carbonate precipitant was a mixed solution of sodium carbonate and sodium hydroxide with a total concentration of 2.5 mol / L, and the concentration of sodium hydroxide was 0.1 mol / L.

[0077] (2) The temperature in the precipitation kettle was maintained at 65° C., and nitrogen was introduced into the kettle. The pH value of the bottom liquid was adjusted to 10.2 using a mixed solution containing sodium carbonate. The rotation speed was 390 rpm and stirring was continued. The iron-manganese mixed solution (100 L / h), the doping solution (11.1 L / h), the complexing agent (25 L / h), and the carbonate precipitant were fed simultaneously for reaction. The feed flow rate of the precipitant was based on ensuring that the pH value was 10.2±0.1. The reaction was continued for 5 h to obtain a precursor seed crystal with a D50 particle size of 1.8 μm.

[0078] (3) After the reaction of step (2) was carried out for 3 hours, the flow rate of the precipitant was appropriately reduced to reduce the pH value to 8.2±0.1, the rotation speed was adjusted to 270 rpm, and the co-flow feeding of the above-mentioned iron-manganese mixed solution and the complexing agent was continued, and the reaction was continued for 130 hours and then stopped. At this time, the target D50 particle size of 13 μm was reached; the stopped material was filtered, washed, dried, and sieved to obtain a coarse rod-shaped oriented iron-manganese-rich precursor (Zn 0.05 Al 0.02 Ti 0.01 Fe 0.46 Mn 0.46 (OH) 0.14 (CO3) 0.95 ).

[0079] (4) The precursor obtained in step (3) and sodium carbonate were weighed and mixed in a molar ratio of 1:0.37, heated and calcined in an air atmosphere, heated to 830°C at a rate of 2°C / min and kept warm for 15h, and finally cooled to room temperature with the furnace to obtain the positive electrode material (Na 0.70 Zn 0.05 Al 0.02 Ti 0.01 Fe 0.46 Mn 0.46 O2).

[0080] According to the molecular formula of the positive electrode material, in this embodiment, δ=0.70, γ=0.46, β=0.46, α=0.08; satisfying: 1.0≥δ≥0.4, 0.65≥γ≥0.4, 0.7≥β≥0.4, 0.10≥α>0, 2.1>δ+γ+β+α=1.7>1.3; in addition:

[0081] 3*γ+(3+z)*β+(2+2z)*α+δ=3*0.46+(3+z)*0.46+(2+2z)*0.08+0.70=4, therefore, z=0.6129, satisfying: 1≥z≥0.

[0082] Example 3

[0083] The method is basically the same as Example 1, except that: in step (1), the complexing agent is a mixed solution of oxalic acid and ammonium acetate, the molar ratio of the two is 1:1, and the total concentration is 1.0 mol / L; the carbonate precipitant is a solution of potassium bicarbonate and sodium hydroxide, the total concentration is 2.5 mol / L, and the concentration of sodium hydroxide is 0.5 mol / L.

[0084] Example 4

[0085] The method is basically the same as Example 1, except that: in step (2), the feed flow rate of the precipitant is adjusted to ensure that the pH value is 10.8±0.2; in step (3), the precipitant flow rate is reduced until the pH value is reduced to 8.8±0.1.

[0086] Example 5

[0087] The process is basically the same as Example 1, except that: in steps (2) and (3), the temperature in the precipitation kettle is maintained at 50°C; in step (4), the calcination temperature is 750°C, and the calcination holding time is 20 hours.

[0088] Example 6

[0089] The process is basically the same as Example 1, except that: in steps (2) and (3), the temperature in the precipitation kettle is maintained at 70°C; in step (4), the calcination temperature is 900°C, and the calcination holding time is 8 hours.

[0090] Comparative Example 1

[0091] It is basically the same as Example 1, except that the calcination temperature in step (4) is 930°C.

[0092] Comparative Example 2

[0093] The process is basically the same as Example 1, except that the temperature in the precipitation kettle is maintained at 40° C. in steps (2) to (3).

[0094] Comparative Example 3

[0095] The same as Example 1, except that: in steps (2) to (3), the flow rate of the doping liquid is increased to obtain an iron-rich manganese precursor (Fe 0.4 Mn 0.4 Ni 0.2 CO3), and then obtain the positive electrode material (Na 0.67 Fe 0.4 Mn 0.4 Ni 0.2 O2).

[0096] Comparative Example 4

[0097] The same as Example 1, except that: the doping solution in step (1) is replaced by a mixed solution of nickel sulfate and titanium sulfate, the concentration of which is 0.8 mol / L, wherein the nickel:titanium concentration ratio is 2:3; the flow rate of the doping solution in steps (2) to (3) is 13.3 L / h, and an iron-rich manganese precursor (Fe 0.45 Mn 0.45 Ni 0.04 Ti 0.06 CO3), and then obtain the positive electrode material (Na 0.67 Fe 0.45 Mn 0.45 Ni 0.04 Ti 0.06 O2).

[0098] Test Example 1

[0099] The precursor and positive electrode material obtained in steps (3) and (4) of Example 1, the positive electrode material obtained in step (4) of Comparative Example 1, and the precursors obtained in step (3) of Comparative Examples 2 to 4 were respectively subjected to scanning electron microscopy examination to obtain corresponding SEM images.

[0100] Figure 2 This is the SEM image of the precursor process sample at 46 hours of reaction in Example 1. It can be clearly observed that the primary particles are oriented in a thick rod shape; Figure 3 is a SEM image of the positive electrode material in Example 1. The morphology still maintains a thick rod-like orientation, indicating that the material structure remains intact after appropriate high-temperature calcination; Figure 4 As shown, the positive electrode material obtained by sintering at a higher temperature in Comparative Example 1 shows that the crystals melt together and the morphology changes. Figure 5 As shown, the SEM image of Comparative Example 2 shows that low temperature is not suitable for the specific growth mode of thick rod-shaped orientation of this type of iron-manganese-rich precursor material. Figure 6 As shown, the SEM image of Comparative Example 3 shows that the large amount of doping elements used has a refining effect on the coarse rod-shaped primary particle morphology of the precursor. Figure 7As shown, by introducing more Ti ions into the comparative example 4, more segregated particles appear in the precursor, destroying the original thick rod-like orientation morphology.

[0101] Test Example 2

[0102] The positive electrode materials obtained in each embodiment and comparative example were dispersed in the solvent NMP with the conductive agent carbon black and the binder polyvinylidene fluoride at a mass ratio of 80:10:10, and then the mixed slurry was coated on the base aluminum foil, dried, rolled, and cut into circular positive electrode sheets; sodium sheets were used for the electrodes, and the electrolyte was sodium hexafluorophosphate solution. The button cells were assembled to test their performance, where the voltage range of the positive electrode material test was 1.5V to 4.0V, and the discharge capacity at current densities of 0.1C, 1C, and 5C was recorded respectively; and the discharge capacity after 100 weeks of discharge at 1C was further recorded.

[0103] Table 1

[0104]

[0105]

[0106] Table 1 shows the rate performance of each embodiment and comparative example at different current densities, as well as the cycle performance at a specific current density. Based on the results in the table, the rate and cycle values ​​of the positive electrode materials obtained in the embodiments are relatively high, indicating that the positive electrode materials maintaining a thick rod-shaped oriented structure have higher electrochemical performance and structural stability.

[0107] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.

Claims

1. An iron-rich manganese-based positive electrode material, characterized in that: The iron-rich manganese-based positive electrode material is a secondary spherical particle or a secondary quasi-spherical particle formed by closely stacking primary particles of a rod-like structure, and the stacking is arranged in a divergent orientation; The molecular formula of the iron-rich manganese-based positive electrode material is Na δ Fe γ Mn β M α O2, M includes at least one of Ni, Ca, Zn, Co, Mg, Al or Ti, 1.0≥δ≥0.4, 0.65≥γ≥0.4, 0.7≥β≥0.4, 0.10≥α>0, 2.1>δ+γ+β+α>1.3; 3*γ+(3+z)*β+(2+2z)*α+δ=4, where z satisfies: 1≥z≥0.

2. The iron-rich manganese-based positive electrode material according to claim 1, characterized in that: The iron-rich manganese-based positive electrode material is prepared by mixing and sintering a precursor and a sodium source; The molecular formula of the precursor is Fe γ Mn β M α (OH) x (CO3) y , y / 2>x≥0, 2.5>2y+x≥2; Set the parameter Q, 70≥Q≥10, to satisfy: 60%≥(55.8*γ+54.9*β+Q*α) / (55.8*γ+54.9*β+Q*α+17*x+60*y)≥40%.

3. The iron-rich manganese-based positive electrode material according to claim 1, characterized in that: The aspect ratio of the primary particles is 3.1 to 8.5, and the radial diameter of the primary particles is 0.4 μm to 0.8 μm; And / or, the D50 of the iron-rich manganese-based positive electrode material is 4.5 μm to 14.5 μm, and the tap density of the iron-rich manganese-based positive electrode material is 1.35 g / cm 3 ~1.95g / cm 3 .

4. The iron-rich manganese-based positive electrode material according to claim 1, characterized in that: M includes M2 with a valence of +2, M3 with a valence of +3 and M4 with a valence of +4. In the iron-rich manganese-based positive electrode material, the atomic contents of M2, M3 and M4 correspond to A, B and C, satisfying: A>B+C>B>C≥0.

5. The method for preparing the iron-rich manganese-based positive electrode material according to any one of claims 1 to 4, characterized in that: The steps include: A mixed solution containing an iron source and a manganese source is prepared, and a doping solution containing a doping element source is prepared; the mixed solution, the doping solution, a complexing agent and a precipitant are simultaneously introduced to perform a precipitation reaction and obtain a precursor; the precursor is mixed with a sodium source and then sintered to obtain an iron-rich manganese-based positive electrode material.

6. The method for preparing the iron-rich manganese-based positive electrode material according to claim 5, characterized in that: The complexing agent includes at least one of ammonia water, oxalic acid, ammonium sulfate, ammonium acetate, citric acid or EDTA-2 sodium; and / or, the precipitating agent comprises at least one of sodium carbonate, sodium bicarbonate, a combination of sodium carbonate and sodium hydroxide, a combination of sodium bicarbonate and sodium hydroxide, potassium carbonate, potassium bicarbonate, a combination of potassium carbonate and sodium hydroxide, or a combination of potassium bicarbonate and sodium hydroxide; And / or, the sodium source includes at least one of sodium carbonate, sodium acetate, sodium hydroxide or sodium bicarbonate.

7. The method for preparing the iron-rich manganese-based positive electrode material according to claim 5, characterized in that: The precipitation reaction includes a seed preparation stage and a growth regulation stage; In the seed crystal preparation stage, the feed amount of the precipitant is controlled to obtain a reaction solution with a pH of 9.5 to 11; this stage is terminated when the seed crystal D50 is 0.1 μm to 2.5 μm; In the growth regulation stage, the feed amount of the precipitant is controlled to obtain a reaction solution with a pH of 7.3 to 9; this stage is terminated when the D50 of the precursor is 5 μm to 15 μm.

8. The method for preparing an iron-rich manganese-based positive electrode material according to claim 5, characterized in that: The temperature of the precipitation reaction is 50°C to 70°C, and the precipitation reaction is carried out under stirring; And / or, the sintering temperature is 750° C. to 900° C., and the sintering time is 8 h to 20 h.

9. A sodium ion battery, characterized in that: It comprises the iron-rich manganese-based positive electrode material as described in any one of claims 1 to 4.

10. An electrical device, characterized in that: Comprising the sodium ion battery as claimed in claim 9.